Upaya Percepatan Pencegahan Dan Penurunan Stunting Melalui Program Pendampingan Keluarga Di Desa Pakuan Kecamatan Narmada - Bq Mekia Rahmayanti; Ruth Stella Petrunella Thei; Dita Ayu Saputri; Sahru Ramdani (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The problem of short children (stunting) is one of the nutritional problems faced in the world, especially in Pakuan village. Stunting is a problem because it is associated with an increased risk of illness and death, sobotimal brain development so that motor development is delayed and mental growth is stunted. Pakuan Village is one of the villages in Narmada sub-district which is the locus of stunting. Based on the stunting data from PSG in Pakuan village in August 2021, in Pakuan village there are 70 children who are stunted, of which 24 children are under two years old. The factors that cause stunting in the village of Pakuan include parenting patterns, lifestyle of pregnant women, unhealthy families, early marriage and there are still many parents who believe in beliefs or myths about the wrong diet of pregnant women in the community. The purpose of this activity is to accelerate efforts to prevent and reduce stunting through a family assistance program in Pakuan village, Narmada sub-district. The method is carried out by carrying out socialization activities, direct family assistance to the Pakuan village community who are the targets and monitoring through posyandu. This activity was realized through collaboration with cadres, village midwives, and the Suranadi Health Center. Based on these activities, the community can understand the pattern of parenting and nutrition given to infants/toddlers at that age in Pakuan village and there are 4 children who experience weight gain, namely Devin Alka, M. Iqbal, Iklal Fikrar, Miatul Febrianti, and Rizki Evarista.